DEVELOPMENT OF LEARNING VIDEO MEDIA ON FINANCIAL SERVICES INSTITUTION MATERIALS TO IMPROVE STUDENT LEARNING OUTCOMES - Ainur Rochmah Ashfiyanti; Putri Ulfa Kamalia (IKIP Widya Darma, 2026)
The purpose of this study was to analyze the feasibility of video learning media, its effectiveness in improving student learning outcomes, and its practicality. This type of research is Research and Development (R&D). The 4D development model was used and implemented only up to the Develop stage. The trial design used was a One-Group Pretest-Posttest design. The research subjects were 36 students from grade X-5 and a team of experts. This research was conducted at SMAN 21 Surabaya. The validation results for the material aspect were 85%, the presentation aspect 87%, the design aspect 84%, and the graphics aspect 83%; thus, the video learning media was declared very feasible for use. The average student learning outcome after treatment with video learning media increased by 34, and the N-Gain test yielded an average of 0.84; thus, the video learning media was declared effective in improving student learning outcomes in the high category. The results of the practicality questionnaire showed an average of 96%, indicating that the video learning media was very practical to use. The results of the study indicate that learning video media is very feasible, effective in improving student learning outcomes, and very practical to use.